2008
DOI: 10.1007/s10552-008-9160-7
|View full text |Cite
|
Sign up to set email alerts
|

Variants in hormone biosynthesis genes and risk of endometrial cancer

Abstract: We investigated the risk associated with variants in three genes involved in estrogen biosynthesis, CYP11A1, CYP17A1, and CYP19A1, in the population-based case control study of Estrogen, Diet, Genetics, and Endometrial Cancer. This study was conducted in New Jersey in 2001-2006 with 417 cases and 402 controls. For CYP11A1, there was no association between the number of [TTTTA] n repeats (D15S520) and risk. For CYP17A1, risk was somewhat lower among women with the C/C genotype at T-34C (rs743572) (adjusted OR=0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 38 publications
(39 reference statements)
0
22
0
Order By: Relevance
“…11,27 Several studies showed that the SNP rs743572 in CYP17A1 appears to be associated with a reduced risk of endometrial cancer, 27,28 but there is some evidence that this SNP increases risk of non-Hodgkin lymphoma. 29 In the present study, we investigated the effects of rs11191548 in Chinese children.…”
Section: Resultsmentioning
confidence: 99%
“…11,27 Several studies showed that the SNP rs743572 in CYP17A1 appears to be associated with a reduced risk of endometrial cancer, 27,28 but there is some evidence that this SNP increases risk of non-Hodgkin lymphoma. 29 In the present study, we investigated the effects of rs11191548 in Chinese children.…”
Section: Resultsmentioning
confidence: 99%
“…Methods in this study have been described in detail elsewhere [18-20]. In brief, the source population for the EDGE study comprised women older than 21 years living in one of these six NJ counties (Bergen, Essex, Hudson, Middlesex, Morris, and Union) and able to understand English or Spanish.…”
Section: Methodsmentioning
confidence: 99%
“…The methods used in the EDGE Study (Estrogen, Diet, Genetics, and Endometrial Cancer) have been described elsewhere [13]. In brief, women older than 21 years and able to understand English or Spanish, and living in one of six NJ counties (Bergen, Essex, Hudson, Middlesex, Morris, and Union) were eligible to participate in the study.…”
Section: Methodsmentioning
confidence: 99%